Psychological Fitness Education Driven by Artificial Intelligence Technology and Its Influence on Education Assessment (Informatica, 2024)
In order to reflect the information reflected by students' psychological fitness data to the greatest extent, this paper explores the improvement strategy of psychological fitness education and its assessment method driven by AI (Artificial intelligence) technology and puts forward a psychological fitness assessment model based on fuzzy mathematics and NN (Neural network) technology. The assessment model can process the data of students' psychological fitness problems and quickly find abnormal data. Based on this, students who may have psychological fitness problems can be identified. In this paper, in the MATLAB simulation tool, the assessment model of psychological fitness education is used to train and learn a certain amount of psychological fitness instructional data. The training experiment demonstrates that the accuracy of the algorithm can reach 95.97%, which is higher than other comparison algorithms. Through the comparison of simulation experiments, the positive significance of the proposed psychological fitness assessment model for AI-driven psychological fitness education is verified.